Congenital aneurysm of the left atrium - Rahman, MM; Pasha, K; Mohsin, MK; Marufuzzaman, S; Habib, SM; Islam, MN; Debnath, RC (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jan;20(1):155-158 The abstract of this article is available on the PubMed website